2006
DOI: 10.1159/000093916
|View full text |Cite
|
Sign up to set email alerts
|

Shock Wave Lithotripsy in Solitary Functioning Kidneys: Is Prophylactic Stenting Necessary?

Abstract: Objective: To assess the safety of shock wave lithotripsy (SWL) without prophylactic stents in solitary functioning kidneys. Patients and Methods: Sixteen solitary functioning kidneys with 23 renal stones with a size of <15 mm were treated with SWL as the primary modality. All patients were counseled about the possibility of obstruction, and treatment was offered to those who consented. The safety of SWL was assessed by the need for interventions and the posttreatment renal function. Results: In 14 patients li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Kumar et al . [ 4 ] shocked 23 renal stones in 16 solitary functioning kidney and concluded that ESWL is safe without prophylactic stents in properly selected and closely monitored patients. Avoiding stent decreases costs, duration of treatment, and stent-related morbidity without unduly compromising safety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kumar et al . [ 4 ] shocked 23 renal stones in 16 solitary functioning kidney and concluded that ESWL is safe without prophylactic stents in properly selected and closely monitored patients. Avoiding stent decreases costs, duration of treatment, and stent-related morbidity without unduly compromising safety.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] and Kumar et al . [ 4 ] do not recommend routine ureteric stenting before ESWL for solitary kidney; however, Karalezli et al . [ 5 ] and Ishii et al .…”
Section: Introductionmentioning
confidence: 99%
“…have shown that SWL monotherapy for renal stones without stenting even in solitary kidneys is safe. [14] In their series of 16 patients with solitary kidneys who underwent SWL monotherapy for renal stones between 5 and 15 mm without stenting, only one patient had complications due to obstruction of ureter. [14] In spite of conflicting reports on pretreatment stenting before SWL monotherapy, our study have emphasized the fact that pretreatment stenting is not mandatory for the success provided closer follow-up is ensured.…”
Section: Discussionmentioning
confidence: 99%
“…Even in patients with a single kidney the procedure without ureteral catheter is feasible, although it requires a careful selection of candidates. 26 A systematic review, 27 using sources such as the PubMed ® , Embase ® and Cochrane databases evaluated the results and complications of ESWL in the treatment of calculi of the upper urinary tract with or without double-J stenting before the procedure. Rate of calculus-free response, steinstrasse, lower urinary tract symptoms, hematuria, fever, infection, pain, dergoing ESWL reported a success rate (defined as patients free of calculi or fragments under 4 mm) of 78% in three months, while 53.1% of these required more than one session and 8.4% had treatment complemented by another procedure (percutaneous nephrolithotomy, flexible ureteroscopy or double-J stenting).…”
Section: Eswl Adjuvant Factorsmentioning
confidence: 99%